Penerapan Sistem Pakar Menggunakan Metode Certainty Factor untuk Diagnosis Penyakit pada Tanaman Jagung - Fivalianda, Dido; Desiani, Anita (UIN Walisongo Semarang, 2024)
Diseases in corn plants are a major factor contributing to suboptimal corn production and can even lead to crop failure. Common diseases in corn include downy mildew and leaf blight. Downy mildew in corn is characterized by symptoms such as khorotil-colored streaks running parallel to the leaf veins, white spots, inhibited growth, and rolled leaves. These symptoms prevent optimal corn growth and may result in total crop failure. This research focuses on developing an expert system to diagnose corn diseases using the Certainty Factor (CF) method. The CF method is designed to provide a degree of certainty in diagnosis or analysis based on symptoms or evidence, especially in situations with limited absolute certainty. The system developed in this study achieves an accuracy rate of 68.74% for diagnosing leaf blight in corn.Keywords: expert system, CF, corn crop disease, downy mildew, leaf blight.